2017
DOI: 10.1177/0265407517712902
|View full text |Cite
|
Sign up to set email alerts
|

Feeling lonely when not socially isolated

Abstract: Although it is widely acknowledged that people can feel lonely when not socially isolated, to our knowledge, no study has examined whether loneliness would be differently associated with daily social relations for people who are not socially isolated. The present study examined the role of social isolation (i.e., small social network size) in moderating the association between loneliness and characteristics of daily social interactions—interaction type and qualitative characteristics—using the 7-day social int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 41 publications
(46 reference statements)
5
22
0
Order By: Relevance
“…Having a partner was not related to loneliness pre-pandemic after inclusion of relevant psychological correlates, which is not in line with previous studies reporting such an association ( Beutel et al, 2017 ; Gyasi et al, 2020 ). Just living together with other individuals was not related to loneliness even without controlling for relevant psychological correlates, pointing toward the importance of the relationship quality ( Wheeler et al, 1983 ; Lee and Ko, 2017 ).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Having a partner was not related to loneliness pre-pandemic after inclusion of relevant psychological correlates, which is not in line with previous studies reporting such an association ( Beutel et al, 2017 ; Gyasi et al, 2020 ). Just living together with other individuals was not related to loneliness even without controlling for relevant psychological correlates, pointing toward the importance of the relationship quality ( Wheeler et al, 1983 ; Lee and Ko, 2017 ).…”
Section: Discussionmentioning
confidence: 89%
“…It is well established that this feeling is not solely related to a low quantity of social interactions. Indeed, poor social interaction quality (i.e., if individuals are lacking in meaningful interactions) is assumed to be one of the strongest predictors of loneliness ( Wheeler et al, 1983 ; Lee and Ko, 2017 ). This presumption suggests that existing feelings of loneliness can be eased by generating more deep and meaningful social interactions ( Hawkley and Cacioppo, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…that other people do not perceive them in the same way that they perceive themselves) and therefore in part to avoidance of further social situations. Similarly, self-focused attention has been suggested to be related to the maintenance of loneliness in both observational (Lee & Ko, 2018) and experimental research (Jones, Hobbs & Hockenbury, 1982). People may perceive their interactions with others in a particular way even if this is not objectively how others perceive them; this type of self-focused attention may be associated with those who subjectively feel lonely even when objectively they are not socially isolated.…”
Section: Studies Identified For Inclusionmentioning
confidence: 97%
“…Thus, based on this approach, it is possible that this lonely in a crowd group, though they have a large network, may be experiencing loss of certain close or important relationships. Very relevant to this discussion, a recent article examined how loneliness and social network size interact to predict day-to-day (closeand weak-tie) social interactions (Lee & Ko, 2017). Results showed that the relationship between loneliness and lower number of day-to-day interactions with close social ties was only statistically significant for those with a greater social network.…”
Section: The Vulnerable Group: Socially Isolated and Lonelymentioning
confidence: 99%